Kadar HbA1c Dapat Mempengaruhi Hasil Pengobatan Fase Awal Pada Pasien Tuberkulosis Paru : HbA1c Levels May Affect Early Phase Treatment Outcomes in Pulmonary Tuberculosis Patients - Febrianti, Mona (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: Pulmonary tuberculosis (TB) is still a health problem in the world. Indonesia is the second country with the highest incidence of pulmonary TB in the world. The high incidence of TB is influenced by the presence of Diabetes Mellitus (DM) in pulmonary TB patients. Methods: In this study, data were obtained from medical records of pulmonary TB patients who were treated at the pulmonary clinic of Matraman Hospital in early November using a total sampling of 36 people. And this research is an observational study with a cross-sectional study design. Results: The study showed that the majority of patients with pulmonary TB at the pulmonary polyclinic of RSUD Matraman were aged patients with the category of young adults (18-44 years) of 11 respondents or 30.6%, while those of middle age (45-59 years) were 19 respondents or 52. 8% and the elderly (≥ 60 years) were 6 respondents or 16.7%., female (52.8%), male (47.2%) and had Hba1c results in the normal category for Pulmonary TB treatment (55.6%) and Hba1c results in the category of Diabetes Mellitus during pulmonary TB treatment (44.4%). The results of the chi-square test showed that there was a relationship between the Hba1c results of pulmonary tuberculosis patients and the effectiveness of the early phase of treatment progress (p = 0.008; OR = 9.000). Discussion: There is a significant relationship between the results of Hba1c in pulmonary tuberculosis patients with the effectiveness of the early phase of treatment progress.